Edukasi Pencegahan Anemia pada Wanita Usia Subur di Desa Tarembang - Abdul Malik Asikin; Nurul Ichsania; Puspita Dewi; Ester G. A Hartiono; Ulfa Purnamasari (Abdimas Toddopuli: Jurnal Pengabdian Pada Masyarakat, 2026)
Anemia among women of reproductive age remains a public health problem that affects quality of life and reproductive health risks. This community service activity aimed to improve the understanding and awareness of women of reproductive age regarding anemia prevention through a participatory educational approach in Tarembang Village. The method integrated behavior change communication and experiential learning through mini workshops, group discussions, simulations, and practice in preparing iron-rich menus based on local foods, without using pre-test and post-test assessments. The participants consisted of 20 women. Evaluation was conducted qualitatively through participatory observation and group reflection. The results showed an increase in participants’ understanding, awareness, and attitudes toward anemia prevention, indicated by their ability to re-explain the material, active involvement during the activities, and commitment to implementing healthy lifestyle behaviors. The peer education approach also supported the potential sustainability of information dissemination within the community. Therefore, participatory and experience-based education proved effective in strengthening anemia prevention efforts among women of reproductive age.